2017
DOI: 10.1007/s10764-017-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Contact Calling Between Black Tufted-Ear Marmosets (Callithrix penicillata) in a Noisy Urban Environment and in a Quiet Forest

Abstract: All habitats have some level of noise but anthropogenic sounds such as those produced by traffic are structurally different from natural sounds, and could cause organisms living in noisy urban areas to modify their vocal communication. We compared temporal and spectral parameters of contact calls in black tufted-ear marmosets (Callithrix penicillata) living in a noisy and a quiet area. From February 2009 to March 2012 we recorded spontaneously produced phee vocalizations by marmosets in two areas in Minas Gera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…18 kHz) were found from the ambient sound that usually occurred in the afternoon [35]. Because marmosets' social behaviours depend on effective vocal communication in such an environment [4345], we hypothesized that adult marmosets could learn about the acoustic environment and subsequently make predictive and long-lasting modifications of the spectrotemporal structure of their vocalizations to facilitate vocal communication with conspecifics. If marmosets were able to decipher the spectral contents of interfering sounds and modify their vocalizations to avoid spectral overlap, we would expect a directional shift in the spectra of their calls away from the interfering sounds.…”
Section: Resultsmentioning
confidence: 99%
“…18 kHz) were found from the ambient sound that usually occurred in the afternoon [35]. Because marmosets' social behaviours depend on effective vocal communication in such an environment [4345], we hypothesized that adult marmosets could learn about the acoustic environment and subsequently make predictive and long-lasting modifications of the spectrotemporal structure of their vocalizations to facilitate vocal communication with conspecifics. If marmosets were able to decipher the spectral contents of interfering sounds and modify their vocalizations to avoid spectral overlap, we would expect a directional shift in the spectra of their calls away from the interfering sounds.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that noise pollution can affect the behaviour, reproduction and survival of wild animals living in cities (Slabbekoorn & Peet, 2003;Warren et al, 2006;Bonier et al, 2007;Duarte et al, 2011;Santos et al, 2017). However, most of these studies are experimental and made under controlled conditions, usually with a single species (Berger-Tal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All habitats have some level of anthropogenic noise, but urban sounds produced by cars, motorcycles, trains, and airplanes, in addition to the sounds produced in buildings and industries, are significantly different from most natural sounds because most of their energy is concentrated in low frequencies (below 2000 Hz) and has longer duration (Warren et al, 2006;Brumm, 2006;Slabbekoorn & Ripmeester, 2008). High noise levels can mask animal acoustic signals, such as sounds from reproductive partners, alarm calls, parental care and territorial defense songs (Brumm et al, 2004;Santos et al, 2017). The masking effect can force species to use compensatory mechanisms to vocally communicate or abandon noisy areas (Nemeth & Brumm, 2009;Santos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…: Rangel-Negrín et al, 2009;Rimbach et al, 2013;Vanlangendonck et al, 2015;howler monkeys, Alouatta spp. : Martínez-Mota et al, 2007;Behie, Pavelka & Chapman, 2010;Rimbach et al, 2013;Vanlangendonck et al, 2015;Cantarelli et al, 2017), Pitheciidae (titi monkeys, Callicebus nigrifrons: Duarte et al, 2017) and Callithrichidae (marmosets, Callithrix penicillata: Duarte et al, 2011;Santos et al, 2017;tamarins, Saguinus leucopus: Soto-Calderón, Álvarez Cardona & García-Montoya, 2016). For example, black-tufted marmosets (C. penicillata) have been shown to avoid noisy areas of an urban park, irrespective of food availability (Duarte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%